The Role of the Ceria Orphan Care Forum in Improving the Quality of Education and Skills of Orphans in Jurumudi Village, Tangerang City: Peran Forum Peduli Yatim Ceria Dalam Peningkatan Kualitas Pendidikan dan Keterampilan Anak Yatim Di Kelurahan Jurumudi, Kota Tangerang - idham; Milsani; Masturoh; Zalva (Jurnal Pengabdian Masyarakat (Bisma), 2025)
The Cheerful Orphan Care Forum in Jurumudi Village, Tangerang City, is a social institution that focuses on the empowerment of orphans through character education programs, life skills, and religious teaching. This study aims to evaluate the impact of these programs on the development of orphans in the forum. The method used in this study is a descriptive qualitative approach, with data collection through observation, interviews, and documentation. The results of the study show that the character education program has succeeded in shaping orphans to become more independent, disciplined, and caring individuals for others. Skills training such as computers and English provide orphans with skills that are very useful for their future, while religious teaching reinforces moral and ethical values in everyday life. Although these programs have a positive impact, challenges related to limited resources such as funds, facilities, and teaching staff remain major obstacles. Therefore, stronger collaboration is needed between social institutions, governments, communities, and the private sector to ensure the sustainability and effectiveness of these programs. It is hoped that through increased support and resources, the Cheerful Orphan Care Forum can continue to grow and have a wider positive impact on orphans, as well as become an empowerment model that can be applied in various regions in Indonesia.